STUDI KESESUAIAN LAHAN UNTUK TANAMAN BUAH NAGA (DRAGON FRUIT) DI KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Rikki Afrizal (JURNAL PLANOLOGI DAN SIPIL (JPS), 2023)
This study aims to study and analiyze about 1) condition of land characteristics (effective slope on land, slope, elevation, drainage rainfall, soil texture, permeability, soil ph, nitrogen (N), phospohorus (P), kalium (K), for dragon fruit in research area.(2) The level of land suitable of Naga dragon Fruit (3)Spatial distribution of lands suitability. Analysis of the data used desriptive with the sampling area. The land units in research area consisted of two processes from the fluvial and volcanic land forms be samples study,the are : 1)The land form process of fluvial oringin (F) was F1.I.Sw.Qal.Al, F1.Teg.Qal.Al, F1.I.Pm.Qal.Al, F.I.KB.QTt.Reg. 2) the process area of volcanic origin is V1.III.Ht.QTt.Reg, V2.III.KB.QTt.Gle d, V2.III.KB.Qtau.Gle d. The mapping unit used is land units, from overlays of several maps, namely maps of land froms, slopes, land uses, land and geology. This land unit maps used for basic drawing research samples. The results of this study show 2(two) levels of land suitability, very suitable and suitable. Very suitable land unit found in F1 land unit. I.Sw.Qal.Al. found in Nagari Ketaping, Nagari Buayan, Nagari Sungai Buluh, Nagari Kasang and land units.F3.I.Kb.QTt.Al in Nagari Sungai Buluh, suitable land unit found F1 land unit Teg.Qal. Al found in Nagari Ketaping, Nagari Sunngai Buluh, and Nagari Kasang, F1.I.Pm.Qal.Al, found in Nagari Sungai Buluh, Nagari Kasang and Nagari Buayan. V1.III.Ht.QTt.Reg, found in Nagari Sungai Buluh, V2.III.KB.QTt.Gle d, in Nagari Kasang and Nagari Sungai Buluh, V2.III.KB.Qtau.Gle d, in Kasang and Nagari Sungai Buluh. The obstacle land factors are Phosphorus (P), Kalium (K), permeability and rainfall